2020
DOI: 10.3892/ol.2020.11260
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain non-coding RNA GACAT1 promotes development and progression of breast cancer by targeting microRNA-875-3p

Abstract: Role of long-chain non-coding ribonucleic acid (lncRNA) GACAT1 in the development of breast cancer and its possible mechanism were investigated. The levels of GACAT1, microRNA-875-3p and Stonin2 (STON2) in breast cancer tissues and adjacent normal tissues were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The level of GACAT1 in breast cancer cell lines was further explored. The effects of GACAT1 and microRNA-875-3p on cell proliferation and cycle were detected by cell counting kit-8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…GAcAT1 expression was found to be increased in gastric cancer and promoted cancer cell proliferation, invasion, and migration (22). Similarly, overexpressed GAcAT1 drove breast cancer development by facilitating proliferation and cell cycle progression (23). In the present study, GAcAT1 knockdown inhibited proliferation, induced apoptosis, and the cell cycle arrest of NScLc cells, supporting its oncogenic role in different types of cancer.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…GAcAT1 expression was found to be increased in gastric cancer and promoted cancer cell proliferation, invasion, and migration (22). Similarly, overexpressed GAcAT1 drove breast cancer development by facilitating proliferation and cell cycle progression (23). In the present study, GAcAT1 knockdown inhibited proliferation, induced apoptosis, and the cell cycle arrest of NScLc cells, supporting its oncogenic role in different types of cancer.…”
Section: Discussionsupporting
confidence: 65%
“…Research into the ceRNA regulatory network suggested that lncRNAs act as endogenous decoys for miRNAs, which in turn affected the binding of miRNAs to the mRNA targets. GACAT1 was found to target miR-875-3p and regulated breast cancer progression ( 23 ). A recent study reported that GACAT1 modulated ZBTB2 and SP1 mRNA expression levels by sponging miR-149 in gastric cancer ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhong et al 34 showed that GACAT1 was decreased in NSCLC tissues, and knockdown of GACAT1 inhibited cell growth and promoted apoptosis via suppressing miR‐422a. Wang et al 35 indicated that GACAT1 induced breast tumour progression via sponging miR‐875‐3p. However, its role and mechanism in TSCC development have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA MIAT can bind miR-1301-3p through “sponge” effect, and then form lncRNA MIAT/miR-1301-3p/INCENP regulatory pathway with the target gene INCENP of miR-1301-3p, which affects the progress of esophageal squamous cell carcinoma [ 9 ]. A large number of evidences indicate that lncRNA GACAT1 is involved in the occurrence and development of tumors [ 10 12 ]. It is overexpressed in many tumor cells, and inhibition of lncRNA GACAT1 expression can not only terminate cell transformation, but also reverse cell malignant transformation.…”
Section: Introductionmentioning
confidence: 99%